Business school leadership and crisis exit planning : global deans' contributions on the occasion of the 50th anniversary of the EFMD - Cornuel, Eric (Cambridge University Press, 2022)
The European Foundation for Management Development (EFMD) is the largest international accreditation body for business schools, with more than 950 members across 92 countries, including the world's highest-ranked schools. A not-for-profit, mission-led institution, the EFMD plays a central role in shaping a global approach to management education, emphasizing the development of socially responsible leaders. As part of EFMD's fiftieth anniversary celebrations, its President, Professor Eric Cornuel, has edited this volume, featuring contributions from leaders in management education, including the presidents and deans of the top business schools from across the world. Each contribution will address the challenges and dilemmas facing business schools today, with respect to four key themes: the 'higher purpose' of business schools; the social impact of business schools; the internationalization of business schools; and crisis management within business schools, with a special focus on the impact of COVID-19. This volume is also available via Open Access.